Attitudes and Educational Settings: A Correlational Analysis - Sicuan, Syrenzo (Journal of Interdisciplinary Perspectives, 2024)
This study explored the relationship between students' attitudes towards mathematics and their educational settings at Pangasinan State University (PSU) Binmaley Campus. Using a descriptive-correlational research design, data was collected from 160 students across four programs: Criminology, Environmental Science, Fisheries and Aquatic Sciences, and Secondary Education major in Science. A survey questionnaire was administered to gather detailed insights into students' perceptions and experiences in mathematics classes. Results indicated that the majority of participants were in their late teens, with significant representation from 19 and 20-year-olds. Female students constituted 57.5% of the sample. First-year students were the predominant group, highlighting the need for transitional support in higher education. The study found that while students generally agreed that mathematics was important and felt confident in their abilities, it was not necessarily their favorite subject. Perceptions of the educational setting at PSU Binmaley were generally positive, with the highest agreement on the classroom environment being conducive to learning. However, areas such as noise level management and teaching pace received slightly lower scores. Importantly, a significant moderate positive correlation (r = 0.444, p < 0.01) was found between students' perceptions of their educational setting and their attitudes towards mathematics, emphasizing the impact of a supportive learning environment on student engagement. These findings underscored the critical role of tailored educational interventions to enhance mathematics learning and engagement, aligning with broader educational policies and research. The study's insights were valuable for informing strategies to improve mathematics education at PSU Binmaley, fostering a more positive and engaging learning experience.